2020
DOI: 10.1093/jalm/jfaa171
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer Disease Pathogenesis: The Role of Autoimmunity

Abstract: Background In addition to deposits of amyloid β (Aβ) plaques and neurofibrillary tangles, growing evidence demonstrates that complex and multifaceted biological processes can arise during Alzheimer disease (AD) pathogenesis. The recent failures of clinical trials based on the amyloid hypothesis and the presence of Aβ plaques in cognitively healthy elderly persons without AD point toward a need to explore novel pathobiological mechanisms of AD. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 96 publications
0
22
0
Order By: Relevance
“…Therefore, it is speculated that ATCAY-like brain specific proteins may be newly exposed to the blood immune system due to BBB breakdown, generating autoantibodies in the AD pathogenesis 44 . There are a growing number of literatures indicating that natural autoantibodies play a protective or pathogenic role in the pathogenesis of neurodegenerative diseases including AD 47 , 48 . Our results suggest that autoantibody repertoires are changing in the AD pathogenesis, supporting that AD is a autoantibody-related autoimmune disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is speculated that ATCAY-like brain specific proteins may be newly exposed to the blood immune system due to BBB breakdown, generating autoantibodies in the AD pathogenesis 44 . There are a growing number of literatures indicating that natural autoantibodies play a protective or pathogenic role in the pathogenesis of neurodegenerative diseases including AD 47 , 48 . Our results suggest that autoantibody repertoires are changing in the AD pathogenesis, supporting that AD is a autoantibody-related autoimmune disorder.…”
Section: Discussionmentioning
confidence: 99%
“…This could be due to differences between the operating procedures followed for each array and the IP experiment, and between the screened samples (serum pools vs individual sera), suggesting that different methodologies should be simultaneously tried to detect for autoantibody targets. In addition, due to the absence of the overlap of the identified antigens targeted by AD autoantibodies between the methodologies and with previously identified AD autoantibodies in other reports, 19,23,25,60 it cannot be discarded that a fraction of the autoantibodies not further validated by ELISA or Halotag-based bead immunoassay might be rare or personalized autoantibodies with limited diagnostic ability of the disease. Although the validation of the screening phase results using PrEST suspension bead arrays showed that the multiomics approach using planar arrays and MS-based methods increased the number of identified reactive antigens, alternative experiments using native antigens were also performed for a more comprehensive of the targets identified by the IP-MS/ MS approach.…”
Section: ■ Discussionmentioning
confidence: 99%
“…This could be due to differences between the operating procedures followed for each array and the IP experiment, and between the screened samples (serum pools vs individual sera), suggesting that different methodologies should be simultaneously tried to detect for autoantibody targets. In addition, due to the absence of the overlap of the identified antigens targeted by AD autoantibodies between the methodologies and with previously identified AD autoantibodies in other reports, ,,, it cannot be discarded that a fraction of the autoantibodies not further validated by ELISA or Halotag-based bead immunoassay might be rare or personalized autoantibodies with limited diagnostic ability of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alzheimer’s disease (AD) is a neurodegenerative brain disease that leads to the damage and death of brain nerve cells in disease progression. It destroys people’s memory, learning, language, cognition, life, and other abilities, and seriously affects the quality of life of patients and families ( Zhang and Wang, 2015 ; Lam et al, 2021 ; Lim et al, 2021 ). AD risk is also greater later in life for people with cardiovascular disease, high blood pressure, and diabetes.…”
Section: Introductionmentioning
confidence: 99%